PEMODELAN MATEMATIKA MANFAAT JUMLAH RAKAAT SHALAT PADA PEMBAKARAN KALORI DALAM TUBUH - indah nursuprianah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2017)
Salah is a grand Muslim worship that starts with takbir and ends by salam.Salat is also the most important worship after syahadah. The command of salat is stated in Noble Quran, Al Ankabut chapter (Surah): verse of 45. In addition to the following command of salah, in fact the peaceful (tumakninah) salah benefits healthy. Calorie burning in every rakaat (the repetition of a unitÂ in salah) of salah, is able to build healthy body. One rakaat is able to burn around 25 calories. So that, the more rakaat in salah, the more calories burnt in our bodies. Total of burnt calories during salah with tukmaninah in a day is 525 calorie with the following assumptions: 5 times of obligatory (fardhu) salah, 17 rakaats and 2 sunnah (optional) salah 4 rakaats without sunnah rawatib salah. Based on some researches, there are a lot of advantages of salah for physical and mental health. Through this research, the writer has attempted to review the advantage of motion of tukmaninah salah over calorie burning in bodies. The research also indiacates how to create mathematical modelling of the advantage of total rakaat of salah over calorie burning in bodies that eventually affect to health.Â Key words: Mathematical modelling, number of rakaah, calorie burning in body